Problems of Education Based on 21st Century Education in Indonesia - Giantama, M Shepna; Nurjannah, Siti; Rahmawati, Desi (Universitas Negeri Jakarta, 2024)
Background In this modern era, society has entered a period of technological advancement, where almost everyone can access the internet and utilize artificial intelligence (AI). Purpose This study aims to examine various problems faced by the education system in Indonesia, including infrastructure, teaching staff, efficiency, and misuse of AI technology. Design/method/approach his study uses a literature review or library study type of research. This approach is carried out by collecting data through searching and analyzing articles, books, or literature sources that are relevant to the topic of study. Results Based on the results of the literature review, it was found that the inequality of education infrastructure between urban and rural areas hampers the quality of education, especially in remote areas. In addition, teaching staff who are less trained in the use of technology and uneven distribution also affect the quality of teaching. The issue of educational efficiency is also in the spotlight, where the increasing budget has not been managed optimally. On the other hand, misuse of AI technology can have a negative impact on students' dependence on machines and reduced human interaction in the learning process. Contribution/value Therefore, there needs to be a concrete solution through improving infrastructure, teacher training, and wise management of technology to improve the quality of education in Indonesia.